Concepções de infância e sua relação com o conhecimento psicológico em Goiás: um recorte histórico - Silva, Natielly Pryscilla (2019)
The present work aims to investigate through a historical research based on the “Revista de Educação do Estado de Goiás”, which were the conceptions of childhood that existed in Goiás during the period of circulation of the journal and to understand if the psychological knowledge and the process of elaboration of these conceptions are related. This was due to the fact that the magazine functioned as an important communication vehicle of the State in terms of subjects related to education, psychology and childhood, that circulated in the period between 1937 and 1962, passing through different nomenclatures and phases. Its existence was concomitant to the moment of modernization of the territory of Goiás that resulted on a greater focus on childhood and the development of different perspectives about it, as a part of the transformation process, especially through the escolanovista movement. This study was made possible through a documentary analysis and bibliographic review based on books, scientific articles, legislations, dissertations, theses and other publications in which the conceptions of childhood as historical constructions were investigated both in the global context and in Brazil and, above all, in Goiás. It is based on the understanding that psychology keeps a close relationship with education and childhood since its emergence as a science in Brazil and Goiás, which contrasts with the existence of a reduced amount of academic research involving history and psychology on a regional context, analyzing from what moment the psychology collaborates with the reflections about the goiana childhood. The research allowed to find a vision of the child followed by the moralizing burden, related to the history of the education of children and children traditionally marked by proposals that aim to follow and favor the natural development of the child, isolating it as a unique element of the pedagogical relationship and displacing its historical, cultural and social roots.